ASTROTOURISM: A LITERATURE REVIEW AND FRAMEWORK FOR FUTURE RESEARCH - Alberto Tapada; Carla Susana Marques; Carlos Peixeira Marques; Carlos Costa (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2021)
Astrotourism consists of activities focused on observing night skies and celestial phenomena in natural spaces, which contributes to communities’ involvement, empowerment and participation and to regional development. In addition to documenting the increased academic research on astrotourism, this literature review sought to construct a general theoretical framework for this field by analysing scholars’ contributions and highlighting the ways in which this topic has been viewed over time. The analyses were based on the academic publications on astrotourism indexed in the Scopus and Web of Science databases up to 2019. A total of 61 documents were subjected to a selection process and eligibility analysis until the sample was reduced to a final set of 42 articles. Qualitative methods were applied to cluster the articles into three themes and analyse each document. This study appears to be the first literature review focused on astrotourism. The results highlight the most researched themes over the years, investigations’ characteristics and gaps in the literature that open doors for future empirical research. The main issues already addressed by the academic community are related to the problems of light pollution, sustainability and regional development, among others, but much room remains for other studies.